DHAWA (WOODFORDIA FRUTICOSA (L.) KURZ.): A VERSATILE MEDICINAL PLANT (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Woodfordia fruticosa is an important medicinal plant used in traditional system of medicine since the time immemorial. It belongs to the family Lythraceae. Many organic constituents like tannins, phenols, steroids/terpenoids, carbohydrates, resins and inorganic ones including iron, aluminum, calcium, magnesium, potassium etc., have been isolated from this species in recent times. Extracts and metabolites of this plant, particularly those from flowers and leaves, possess useful pharmacological activities. Flowers are qabiz (astringent), mubarrid (refrigerant), habisud dam (haemostatic), qatil kirme shikam (anthelminthic), mujaffif (dessicative), mundamil qurooh (enhance wound healing) musakkin atsh, musaffi khoon etc. It is commonly used to cure ishaal (diarrhoea), kasrate tams (menorrhagia), and bawaseer damvia (bleeding piles). Aabzan (sitz bath) with decoction of this drug is useful for khuroojul miqad (prolapse of anus) and sailanur rehem (leucorrhoea). The bark is also pungent, acrid, cooling, toxic, alexatric, antihelmintic, antidysentric, and uterine sedative. The bark is used in thirst, dysentery, leprosy, erysipelas and diseases of the blood. Antitumor, DNA inhibitory, immunomodulatory, antioxidant, aniproliferative, antihyperglycemic, anti-inflammatory, analgesic, cytotoxic, antibacterial, hepatoprotective, antimicrobial and anti-ulcer activities were found in various parts of this plant. Ethnopharmacological activities, chemical component and related pharmacological effects reveal that the plant Woodfordia fruticosa is an important medicinal plant having versatile beneficial pharmacological effects.